Evaluating protein to energy ratios on the growth, survival, and immune response of juvenile Giant trevally (Caranx ignobilis Forsskal, 1775) fed various fish hydrolysates as fishmeal supplementation - Nguyen, Minh Chau (Curtin University, 2024)
A series of three feeding experiments were conducted. The results showed that the growth of giant trevally was improved by (i) 52% protein and 10% lipid with a P/E ratio of 24.63 g/MJ in diets, (ii) dietary supplemented TH or SH levels of 30-60 g/kg, and (iii) the supplementation of 45 g/kg SH in the diet with protein sources from FM and MBM.